2022
DOI: 10.3389/fnut.2022.1012087
|View full text |Cite
|
Sign up to set email alerts
|

The effects and significance of gut microbiota and its metabolites on the regulation of osteoarthritis: Close coordination of gut-bone axis

Abstract: Osteoarthritis (OA) is a common chronic degenerative disease of articular cartilage in middle-aged and older individuals, which can result in the joint pain and dysfunction, and even cause the joint deformity or disability. With the enhancing process of global aging, OA has gradually become a major public health problem worldwide. Explaining pathogenesis of OA is critical for the development of new preventive and therapeutic interventions. In recent years, gut microbiota (GM) has been generally regarded as a “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 160 publications
0
11
0
Order By: Relevance
“…The gut–bone signaling axis has become increasingly evident as a major contributor to bone health. , The gut microbiota contributing to bone mass has been proved by germ-free mice . The concept of “osteomicrobiology” has been gradually proposed to emphasize the gut–bone signaling axis. , In this study, an OVX mouse model with osteoporosis was established, and dietary IQ was able to effectively improve the disruption of intestinal flora and gut barrier function caused by OVX.…”
Section: Discussionmentioning
confidence: 96%
“…The gut–bone signaling axis has become increasingly evident as a major contributor to bone health. , The gut microbiota contributing to bone mass has been proved by germ-free mice . The concept of “osteomicrobiology” has been gradually proposed to emphasize the gut–bone signaling axis. , In this study, an OVX mouse model with osteoporosis was established, and dietary IQ was able to effectively improve the disruption of intestinal flora and gut barrier function caused by OVX.…”
Section: Discussionmentioning
confidence: 96%
“…A growing number of studies have shown that an imbalance in intestinal homeostasis may induce several extrenteral immune and metabolic diseases (such as osteoporosis, OA, psoriasis, and systemic lupus erythematosus) ( 37 39 ). The intestinal flora is a key factor in activating and maintaining intestinal physiological functions and plays an indelible role in maintaining the health and homeostasis of the host ( 7 ). In recent years, an increasing number of human and animal studies have indicated the presence of the gut axis and recognized that the gut joint axis and gastrointestinal microbiome-induced immune and inflammatory responses play an important role in joint health ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both diseases are described as age-related. Due to the high prevalence of OA and OP and their heavy burden on patients and the function of social medical services, OA and OP have gradually become an ongoing focus in current scientific research ( 7 ). Studies have shown that both OA and OP are closely related to the equilibrium state of the gut microenvironment, suggesting a potentially important factor imbalance in the gut microbiota ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the future, diet, fecal transplantation, and future therapies targeting the microbiota are estimated to be approached in all diagnostic and therapeutic protocols. Consequently, diet control (especially foods with low gluten content and enriched in indigestible B) could open new scientific horizons in the occurrence and monitoring of OA pathology [ 6 , 31 , 32 , 33 , 34 ]. More and more studies have shown that the reduced buffering capacity of saliva is related to periodontal disease and caries.…”
Section: Oral Microbiome In Mouth and Systemic Diseasesmentioning
confidence: 99%